The Possibility of the High Voltage Testing in Renewable Energy Power Facilities - Simić, Ninoslav P (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
The paper presents the possibility of using high voltage tests in acceptance tests in the power facilities of renewable energy sources. The practical problems that present them to the examiners on site and the ways to overcome them are described. Special emphasis is given to the testing of power cables, because these tests are particularly demanding. Realistic test results of busbars and cells of metal-enclosed switchgear, power cables and surge arresters are presented with interpretations, comments and recommendations.